Biocompatible Materials Enabled by Biobased Production of Pyomelanin Isoforms Using an Engineered Yarrowia lipolytica. (5th November 2021) - Miller, Kelly K.; Springthorpe, Sarah K.; Imbrogno, Jennifer; Walker, David J. F.; Gadiyar, Shruti; Keitz, Benjamin K.; Ellington, Andrew D.; Lynd, Nathaniel A.; Alper, Hal S.
Abstract: Melanin‐like compounds have been studied in recent years for their electron transport and ultraviolet (UV) light absorbance properties as well as applications as functional, biocompatible catalysts, and material additives. Pyomelanin is a unique form of melanin compounds that has not received significant attention. Here, a strain of Yarrowia lipolytica suitable for the production of nearly 2.8 g L −1 of homogentisic acid (HGA) is metabolically engineered, which can then be oxidized to form pyomelanin either in situ or through altering pH. By using this biosourced material, a series of material traits including spectral analysis/UV–vis absorbance properties, electronic and metal interaction/chelation properties, and effectiveness in polymer dispersions with poly(l ‐lactide) are evaluated. In all cases, biosourced pyomelanin performs on par with or better than a chemically sourced analog. In a performance application, it is explored how pyomelanin may be blended at low concentrations to increase the elasticity of a rigid commercial polymer. Collectively, this work establishes biosourced pyomelanin as a versatile compound for unique material applications. Abstract : This work metabolically engineers a strain of Yarrowia lipolytica for the rapid production of homogentisic acid that can be in situ or post‐hoc converted into pyomelanin. Unique material traits of pyomelanin compounds are explored in applications including electronic materials, metal chelation, and polymer additives. This work establishes pyomelanin as a new functional material complementing ongoing work with melanin and eumelanin.